Different Induction of PD-L1 (CD274) and PD-1 (CD279) Expression in THP-1-Differentiated Types 1 and 2 Macrophages - Lai CY (Dove Medical Press, 2021)
Chun-Yi Lai,1,2,* Po-Chun Tseng,1,2,* Chia-Ling Chen,3 Rahmat Dani Satria,2,4– 6 Yung-Ting Wang,2 Chiou-Feng Lin1,2,7,8 1Core Laboratory of Immune Monitoring, Office of Research & Development, Taipei Medical University, Taipei, 110, Taiwan; 2Department of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, 110, Taiwan; 3School of Respiratory Therapy, College of Medicine, Taipei Medical University, Taipei, 110, Taiwan; 4International Ph.D. Program in Medicine, College of Medicine, Taipei Medical University, Taipei, 110, Taiwan; 5Department of Clinical Pathology and Laboratory Medicine, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada, Yogyakarta, 55281, Indonesia; 6Clinical Laboratory Installation, Dr. Sardjito Central General Hospital, Yogyakarta, 55281, Indonesia; 7Graduate Institute of Medical Sciences, College of Medicine, Taipei Medical University, Taipei, 110, Taiwan; 8International Ph.D. Program in Cell Therapy and Regenerative Medicine, College of Medicine, Taipei Medical University, Taipei, 110, Taiwan*These authors contributed equally to this workCorrespondence: Chiou-Feng LinDepartment of Microbiology and Immunology, School of Medicine, College of Medicine, Taipei Medical University, Taipei, 110, TaiwanTel +886 2 27361661 ext. 7156Email cflin2014@tmu.edu.twBackground: Phorbol 12-myristate 13-acetate (PMA)-induced differentiation of human monocytic THP-1 cells is an experimental model for preparing resting macrophages (M0) for cell polarization toward the different functional specializations of macrophages.Methods: In this study, we examined the expression of immune checkpoints by using flow cytometry following multicolor staining. The blockade of immune checkpoint by using neutralizing antibodies was performed to assess their role in PMA-induced THP-1-differentiated macrophages.Results: Upon the inducible macrophage differentiation caused by PMA, increased expression levels of CD11b and CD68 were measured and characterized according to their adherent phenotype accompanied by the generation of cellular complexity. While the cell growth rate was abolished post-differentiation, some cells underwent cell death. Notably, we found increases in the expression of programmed cell death protein 1, also known as PD-1 (CD279), and its ligand PD-L1 (CD274), mainly in differentiated M0 (CD68+CD11b+) macrophages. However, neutralizing PD-L1/PD-1 neither blocked THP-1 cell differentiation toward macrophages nor inhibited macrophage polarization in M1 and M2. In specializing macrophages, a decrease both in CD274 and CD279 was found in M2.Conclusion: These results revealed the inducible expression of PD-L1/PD-1 in PMA-induced THP-1-differentiated M0 macrophages followed by a decrease in M2 macrophages.Keywords: PMA, THP-1, macrophage, differentiation, PD-L1, PD-1